An in situ assembly of a DNA–streptavidin dendrimer nanostructure: a new amplified quartz crystal microbalance platform for nucleic acid sensing1. Issue 53 (7th July 2015) - Zhao, Yan; Wang, Huaming; Tang, Wei; Hu, Shichao; Li, Na; Liu, Feng
<x xml:space="preserve">Abstract</x> A target-triggered in situ assembly of a DNA–streptavidin dendrimer nanostructure was developed to create a facile platform for nucleic acid sensing.